Metabolomics-Based Profiling of Antioxidant Compounds in Kesum (Polygonum minus) via UHPLC-Q-Orbitrap HRMS as Potential Anti-SARS-CoV-2 Candidates: An In Silico Approach - Iche Azani; Dini Hadiarti; Arni Arni; Nur Aulia Fitri (Biology, Medicine, & Natural Product Chemistry, 2026)
Kesum or Polygonum minus (P. minus) is well-known for its high antioxidant content and potential as a therapeutic agent. This study aimed to identify active compounds in P. minus leaf extracts that serve as antioxidants and SARS-CoV-2 inhibitor candidates using metabolomics approach. P. minus leaves were extracted with ethanol and subsequently fractionated using n-hexane, ethyl acetate, and water. The ethyl acetate fraction exhibited the highest antioxidant activity as measured by the DPPH method. Further analysis using UHPLC-Q-Orbitrap HRMS identified several compounds, including 3-hydroxybenzoic acid, quercetin-3betha-D-glucoside, tectoridin, apigenin, hispidulin, and (±)-usnic acid. These compounds were subsequently evaluated in silico by molecular docking against the 1OG5 and 7CMD target proteins. The results demonstrated strong interactions between these compounds and the protein active sites, supporting their potential as both antioxidants and inhibitors of SARS-CoV-2. This study suggests that P. minus is a promising source of bioactive compounds for development in herbal-based therapies in West Kalimantan.